Budget Gaming: When Accountants Become the Main Players - MANUARI, Ida Ayu Ratih; NIDA, Desak Rurik Pradnya Paramitha; INDRIANI, Eni (PT Keberlanjutan Strategis Indonesia, 2024)
budget gaming conducted by accountants. Budget gaming is suspected to occur due to the lack of transparency in achieving budget targets. Public trust plays a major role in the sustainability of the accounting profession.This study uses a quantitative approach with a quota sampling method to collect data from 85 respondents, consisting of government and private accountants in Bali. Data were obtained through a 5-point Likert scale-based questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study indicate that performance pressure and performance evaluation systems have a significant influence on budget gaming, while perceptions of procedural justice do not show a significant influence. The ethics of the accounting profession are also unable to moderate the relationship between independent and dependent variables.This study provides a real contribution to organizational management by suggesting improvements to the performance evaluation system to be fairer and more comprehensive and wiser management of work pressure through realistic targets and support for employees. This study also enriches the literature on budget gaming behavior, especially in the context of work culture and the economy of tourism areas. By focusing on the role of accountants, this study provides strategic insights for the development of more transparent and accountable budgeting policies.